DEVELOPMENT OF READING SKILLS OF FREE-THINKING STUDENTS IN EDUCATIONAL INSTITUTIONS (Web of Teachers: Inderscience Research, 2023)
The article discusses the role of the family and the activities and duties of adults in the development of reading skills of free-thinking students in higher educational institutions, in creating a culture of reading. Also, students were told to improve oral and written literacy through the analysis of artistic works, to form cultural communication competitions by creating dialogic and monologic texts, and that artistic works are spiritual food for a person to understand life.